Infrastructures of the System for Developing Electronic Health Record - Moghaddasi, Hamid; Hosseini, Azamossadat; Asadi, Farkhondeh; Ganjali, Raheleh (Archives of Advances in Biosciences, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The overall objective of a health system is to improve health through reducing disease, disability and death. Accomplishment of this goal depends on the worldwide integrated and coordinated care continuity. Information transmission is a prerequisite to ensure the continuity of care. Widespread acceptance of health information and communication technology (HICT) and developing systems such as Electronic Health Record (EHR), have changed the health care industry. Electronic Health Record is the main part of information management in an integrated health care system. Electronic health record provides access to all health information at organizational, regional, national and international levels and allows for the patient's health data [usually with geographical distribution in several health information systems] to become integrated. Since Electronic health record integrates all care events data, it can make data sharing possible between all care providers to consequently minimize the repeated diagnostic tests, and drug and treatment interactions. Furthermore, Also health care professionals can easily access to patient information at any time and this could lead to improving the quality of care and reduce costs. Accordingly, a productive system is required to provide the electronic health record. Given the significance of the electronic health record and its generating system in improvement of care quality and reducing the health care costs, authors decided to study the needs for developing the national EHR system (NHIN) The main focus of this paper was on selecting material related to the system developing an EHR and it prerequisites. Electronic health record system is a new source of valuable intelligence of real world for the whole health care industry. Electronic health record system includes people, rules, standards, storage and processing equipments, communication and support facilities. To shape this, existence of components and their coordination is necessary. Electronic health record system are established to enhance patient care and its outcome, increase efficiency, improving the availability of information and minimizing the medical errors. With the Europe union formation that in fact was an important step toward globalization, the electronic health record passed the national borders and turned into a global concept to make possible the worldwide integration and sharing of the health data. Therefore international standards are needed to share patient health information between national health systems and across borders. Infrastructure or national information network existence of proper hardware and software and finally participation of all stakeholders are necessary to develop the system. So it is necessary to prepare the infrastructures needed for development of the system in our country. Since EHR has a universal concept, it is needed to create a lifelong health information record for every individual accessible in every point in the world.